Use of Photodynamic Therapy for Treatment of Actinic Keratoses in Organ Transplant Recipients. (24th December 2012) - Wlodek, Christina; Ali, Faisal R.; Lear, John T.
Abstract : Solid organ transplant recipients are predisposed to actinic keratoses (AK) and nonmelanoma skin cancers, owing to the lifelong immunosuppression required. Today, increasing numbers of organ transplants are being performed and organ transplant recipients (OTRs) are surviving much longer. Photodynamic therapy (PDT) is proving a highly effective treatment modality for AK amongst this susceptible group of patients. Following an overview of the pathogenesis of AK amongst OTRs, the authors review current safety and efficacy data and how this relates to the role of PDT for the treatment of AK in OTRs.